Evasion of interferon-mediated immune response by arteriviruses - Jian, Zhijie; Ma, Rui; Zhu, Ling; Deng, Huidan; Li, Fengqin; Zhao, Jun; Deng, Lishuang; Lai, Siyuan; Sun, Xiangang; Tang, Huaqiao; Xu, Zhiwen (Frontiers in Immunology, 2022)
IFN is the most potent antiviral cytokine required for the innate and adaptive immune responses, and its expression can help the host defend against viral infection. Arteriviruses have evolved strategies to antagonize the host cell's innate immune responses, interfering with IFN expression by interfering with RIG, blocking PRR, obstructing IRF-3/7, NF-κB, and degrading STAT1 signaling pathways, thereby assisting viral immune evasion. Arteriviruses infect immune cells and may result in persistence in infected hosts. In this article, we reviewed the strategies used by Arteriviruses to antagonize IFN production and thwart IFN-activated antiviral signaling, mainly including structural and nonstructural proteins of Arteriviruses encoding IFN antagonists directly or indirectly to disrupt innate immunity. This review will certainly provide a better insight into the pathogenesis of the arthritis virus and provide a theoretical basis for developing more efficient vaccines.